Depressão em crianças: sintoma ou inibição? - Bayma, Manuella Bachá Joca (2015)
The aim of this study is centered on the discussion of possible incidences of childhood depression, and is based on a counterpoint between the psychoanalytic concepts of symptom and inhibition. The question that guides this work is: There is a relationship between the depressive position and inhibition from the latency period? If so, on what terms this relationship can be thought and what are the consequences for the direction of the treatment? With respect to methodology, it is a qualitative study, anchored in psychoanalysis, where we take the theoretical propositions of Freud and Lacan, and also authors who talked about depression, like Mauro Mendes Dias, Irene Kuperwajs, Maria Rita Kehl e Astréa da Gama e Silva, among others. The results show that the concepts of symptom, inhibition and anguish expand knowledge about depressive disorder in children, allowing reflections on the management and direction of analytic treatment in such cases. As a conclusion, we highlight the relevance of the distinction between symptom, inhibition and anguish, in that inhibition and anguish concern the psychic constitution process, may be taken as evidence of a change in subject position.